KONSTRUKSI SOSIAL TENTANG LITERASI KESEHATAN DALAM MERESPON PANDEMI COVID 19 - Novia Ul Haq; Sri Sadewo (Jurnal Pendidikan Kesehatan, 2021)
This article discusses the social construction of the community regarding health literacy in responding to the Covid 19 pandemic. Health literacy is very necessary, especially during the current pandemic. The amount of information in the mass media requires the public to examine it more deeply so that the information received can be implemented properly. The writing of this article uses descriptive qualitative analysis techniques with information collection techniques sourced from informants in the field and observation as the main source, while journals and articles that match the title of the study become supporting data. The data obtained will be analyzed using social construction theory by Berger and Luckmann. The results obtained are the lack of health literacy in responding to the Covid 19 pandemic, which is shown in the behavior of people who do not implement health protocols. Therefore, the government and the community must collaborate in improving health literacy in order to be able to manage information properly.